The empty ballot phenomenon in regional head elections from the perspective of the theory of communicative action - Ayunda Hariyanti; Sufyanto (Universitas Islam Malang, 2026)
The phenomenon of single-candidate pairs and the presence of empty boxes in Regional Head Elections (Pilkada) pose political communication challenges for election organizers in building public understanding. The 2024 Gresik Regency Election, which was contested by only one candidate pair and resulted in 40.28% of the votes going to blank ballots, serves as the empirical context for this research. This research aims to analyze the political communication strategies of the Gresik District General Election Commission (KPU) in socializing the blank ballot using Jürgen Habermas's theory of communicative action. The research uses a qualitative approach with an instrumental case study design, employing interviews, observations, and documentation. The research findings indicate that the KPU's communication strategy tends to be dominated by instrumental rationality oriented toward procedural and regulatory compliance. The information has been factually presented, claims of truth and neutrality have been maintained, and claims of accuracy have been made. However, the limitations of public dialog have resulted in claims of honesty and comprehensibility not being optimally fulfilled. As a result, empty boxes are more often interpreted as an expression of political protest. The novelty of this research lies in the analysis of the General Election Commission (KPU) as a communicative actor that reveals the dominance of instrumental rationality in the socialization of blank ballots in single-candidate regional elections.